Paleogene larger rotaliid foraminifera from the western and central Neotethys - Hottinger, Lukas; Bassi, Davide (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book provides a representative assessment of the state of the art of research on Paleogene rotaliid larger foraminifera. It gives an overview of the current understanding of systematics of this group and, in particular, of its biostratigraphic importance and palaeobiogeography. The senior author of the work, late Professor Hottinger, a leading scientist in the field, both from a systematic and applied side, presents in this book his most recent advances. The foraminiferal family Rotaliidae is a traditional group used frequently which plays an important role for petroleum exploration in the biostratigraphy and palaeobiogeography of Paleogene shallow water deposits in the Middle East. This book aims to introduce rotaliid representatives as index fossils that can be recognized in random thin-sections of cemented rocks. The book is generously illustrated with an unprecedented degree of accuracy. The selection of taxa is restricted to forms having lived in the Paleocene and the Eocene, where their biostratigraphic significance is much higher than during later epochs. However, some additional rotaliid taxa, from the Late Cretaceous or that do not belong to the family Rotaliidae sensu stricto, are included in this book in order to demonstrate particular roots of rotaliid phylogenetic lineages in the previous community maturation cycle or to delimit the taxon Rotaliidae with more precision. This book can be considered as a reference in the field.
Rotaliid shell architecture and the palaeodiversity of the Lockhartia Sea -- The system of the Rotaliidae, an overview -- Subfamily Rotaliinae Ehrenberg, 1839 -- New subfamily Redmondininae -- New subfamily Lockhartiinae -- New subfamily Kathininae -- New subfamily Daviesininae -- Some taxa that are or remain excluded from the family Rotallidae -- Rotaliid taxa with uncertain affinities.
Description based on publisher-supplied MARC data.
Keywords: Economic geology; Fossil fuels; Geobiology; Paleontology .; Paleontology; Biogeosciences; Economic Geology; Fossil Fuels (incl. Carbon Capture).